Effects of Some Nutrient Elements on 2-Acetyl-1-pyrroline Production in Thai Hom Mali Rice Grown Under Hydroponic System - Sakon Monggoot (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Thai Hom Mali rice (Thai fragrant rice) is one of the most important exported products of Thailand. 2-Acetyl-1-pyrroline (2AP) is the key odorant as a quality indicator of Thai Hom Mali rice. The quality of Thai Hom Mali rice is depended on cultivation, post-harvest management, climate and soil quality. Therefore, this study was emphasized on nutrient management for enhancing 2AP production in Thai Hom Mali rice. Experimentation included single nutrient element treatments in which nitrogen (N), phosphorous (P), calcium (Ca), zinc (Zn), Manganese (Mn) or Magnesium (Mg) was invidually studied at 2, 4 and 8-fold from its standard concentration, and nutrient element formula treatments which were designed with central composite design (CCD). The rice was cultivated in hydroponic system by using Hoagland (1938) standard nutrient solution. 2AP content was analyzed with gas chromatography-nitrogen phosphorous detector (GC/NPD). Considering Pathum Thani 1 crop, it was found that adding extra amount of any single element could negatively affect on production of 2AP. However, among the single element treatments, it was obvious that P could have positive influence on 2AP production, and that N showed negative response in production of 2AP greater than Ca, Mn and Mg. The nutrient element formulas with high P were likely to have positive effect on 2AP production. The most effective formulas on 2AP production are formulas number 12 (low Ca and N, and high P, Zn, Mn and Mg) and 13 (low N, Zn, Mn and Mg and high P and Ca). For Khao Dawk Mali 105 crop, it was found that all single nutrient element additions could result in increasing amount of 2AP, compared with the controls. 2AP content in the control was 1.42 and 1.22 ppm, and 2AP in rice treated with 2, 4 and 8-fold of P were 16.68, 7.70 and 3.12 ppm, respectively. From the experiment, the concentration of nutrient element at 2-fold affected 2AP production more than the other concentration levels (4 and 8-fold). It appeared likely than N was to have negative effect, but P, Ca, Mn, Mg and Zn were to have positive effect on 2AP production. However, the concentration level of P was positively correlated with Ca, Mn, Mg and Zn in enhancing effect of 2AP production. The good management of nutrient element is important and needed for enhancing of Thai Hom Mali rice’s quality. This research would be a part of solution for improving and sustaining aroma quality of Thai Hom Mali rice.